Overview of Antipsychotic Use in Schizophrenia Patients at the East City Health Center in 2024 - Tuloli, Teti Sutriyati; Makkulawu, Andi; Sumaga, Khairunnisa Alya; Madania, Madania; Manno, Mohamad Reski (Poltekkes Kemenkes Gorontalo, 2025)
Schizophrenia is a severe mental disorder that affects individuals and greatly impacts their families and society, with symptoms like hallucinations, delusions, and emotional or thought disturbances that disrupt daily life and well-being. Treatment for schizophrenia usually involves a combination of antipsychotic drug therapy, psychotherapy, and social support. This study aims to determine the description of antipsychotic use, including the type of drug, rules of use, drug dosage, and duration of use in schizophrenia patients at the Kota Timur Health Center. This study used a descriptive observational research design with data collection using a retrospective method. The research data were obtained from secondary data in the form of medical record data from as many as 25 patients with mental illness. The data were processed with Excel and analyzed using SPSS version 26. The results showed that schizophrenia was predominantly suffered by male patients (56%), and more were in the age range of 34-46 years (as many as 48%). The most widely used antipsychotic drugs were a combination of typical and atypical, as many as 92%. The most frequently used type of drug is clozapine with a dose of 25 mg, and the rules of use are 2 x 1/2 as much as 46%. The longest duration of treatment is already in the maintenance phase, which is 96%. Additional drug trihexyphenidyl 2 mg (2 x 1) is used as much as 92%. The most widely used type of therapy is 3-combination therapy, namely Risperidone + THP + Clozapine, as much as 56%. This study was conducted at the East City Health Center, Gorontalo, which is one of the largest primary healthcare facilities in the region and manages a considerable number of schizophrenia patients with limited psychiatric resources. Therefore, the study setting provides important insights into the real-world use of antipsychotic medications in a community-based healthcare center.